Analysis of Students' Learning Styles in Biology Subjects at Madrasah Aliyah Raudlatus Syabab Sukowono Jember - Nasution, Nanda Eska Anugrah; Putri, Mita Utari; Rizka, Chairany (Department of Biology Education, Faculty of Education and teacher Training, Maritime University of Raja Ali Haji, 2023)
This study aimed to delineate the learning style profile of class XI IPA 2 students during biology lessons at Madrasah Aliyah Raudlatus Syabab Sukowono. The research was conducted at Madrasah Aliyah Raudlatus Syabab, located at Jl. KH. Ahmad Syukri No. 02, Sumber Wringin, Kec. Sukowono, Kab. Jember, East Java. This study employs a quantitative descriptive approach. This research techniques involve collecting, recording, presenting, and verifying data. The participants in this study consisted of students from class XI IPA 2 and teachers specializing in Biology. The purposive sampling approach is used for selecting subjects or data sources. The data collection methods employed in this research comprise interviews, questionnaires, observation, and documentation. The research findings indicate that the predominant learning style among students studying biology at Madrasah Aliyah Raudlatus Syabab Sukowono Jember is visual, with 7 individuals (50%) exhibiting this style. This is followed by kinesthetic, with 4 individuals (29%), and auditory, with 3 individuals (21%). Teachers should possess the ability to establish a varied educational setting and integrate learning techniques that encompass the utilization of visuals and graphics, verbal explanations and discussions, as well as experiments and physical activities in order to cater to the diverse learning styles of students.